Hydrochemical characteristic and water quality assessment for drinking and agricultural purposes in District Jacobabad, Lower Indus Plain, Pakistan - Shahab, Asfandyar; Qi, Shihua; Zaheer, Muhammad; Rashid, Audil; Talib, Muhammad Afnan; Ashraf, Umer (International Journal of Agricultural and Biological Engineering, 2018)
Undeniably water is of utmost importance while considering basic necessities. This investigation emphasized on the hydrochemical evaluation and drinking water quality assessment in District Jacobabad located in lower Indus plain, Pakistan. Certainly world's largest irrigation system emerged from Indus Basin, which is underlain by well transmissive aquifer resulting in higher water table. Water supply schemes with their water sources from ground water and surface water provide piped water for drinking purpose to the community. Water samples were collected from all the forty eight supply schemes of which thirty two were found nonfunctional. Analytical parameters were compared with World Health Organization (WHO) and Pakistan Water Quality Standards but adversely substantial samples were found nonpotable. Alkalinity, bicarbonate and nitrate met the standard safe limits while values for EC, TDS, hardness, cations and anions exceeded the limits in numerous samples. SPSS and ArcGIS softwares were used for statistical analysis and spatial distribution of parameters. Hydrochemical facies were developed and suitability assessment of water resources was examined for agricultural use. The ground water type was classified as Na-HCO3 type with high salinity and it required treatment prior to irrigation. The proposed research exhibited the probable drinking water contamination sources and it demanded instant actions to further protect the valuable drinking water resources in District Jacobabad.Keywords: water quality assessment, water supply schemes, drinking and agriculture, arsenic, ArcGIS, PakistanDOI: 10.25165/j.ijabe.20181102.2747Citation: Shahab A, Qi S H, Zaheer M, Rashid A, Talib M A, Ashraf U. Hydrochemical characteristics and water quality assessment for drinking and agricultural purposes in District Jacobabad, Lower Indus Plain, Pakistan. Int J Agric & Biol Eng, 2018; 11(2): 115–121.